Plan de marketing para incrementar las ventas del Bar Coco Compa - Cárdenas Reyes, Maybeline Lorelain (2022)
The theme "Marketing Plan to increase sales of the Bar Coco Compa", presented the problem of the decline in economic activities that have harmed the financial part and the decrease in the commercial operations of its products. From this point of view, the general objective arose of developing a marketing plan aimed at increasing sales of the Coco Compa bar, which justified the investigation in the theoretical part with the background, taken from other investigations and theories of different experts who were part of the theoretical, conceptual and legal framework. It was important to highlight that the literary review gave light to broaden the knowledge on the topic raised. In the methodological part, the deductive and analytical method was used, with a mixed, qualitative and quantitative approach, carried out through interviews and surveys. The population and sample for the survey were 383 clients of the company under study and the interviews were conducted with the general manager and clients of the company. In the results, it was obtained that the implementation of a marketing plan with strategies that allow increasing the sales of products and services to improve sales is required, therefore, the two variables and the results that allow the fulfillment of the objectives were compared. raised. The conclusions showed that home delivery strategies and opening another market niche are necessary to strengthen sales, obtaining B/C= $1.13; that is, for every dollar, 0.13 cents would be earned.